The Criminalization of YouTube Prank Content: A Legal Review through Indonesian ITE Law and Islamic Criminal Law in the Digital Era - Faizatul Nasifa; Nurjannah, ST. (MUI Sulawesi Selatan, 2024)
This study aims to analyze the legal status of prank content produced by YouTubers, particularly through the lens of Indonesia’s Electronic Information and Transactions Law (ITE Law) and Islamic Criminal Law. The research is motivated by the rise of prank videos that potentially cause harm and violate ethical and legal norms. Using a qualitative library research method grounded in a normative juridical approach, this study employs three legal perspectives: the statute approach, case approach, and syar’i (Islamic legal) approach. Data were sourced from primary, secondary, and tertiary legal materials and analyzed using descriptive-analytical techniques. The findings reveal that although the ITE Law does not explicitly regulate prank content, certain prank videos—such as those created by YouTuber Ferdian Paleka—fulfill the criteria for violations under Article 27 paragraphs (1) and (3), in conjunction with Article 45 paragraphs (1) and (3) of the ITE Law, concerning indecency, defamation, and public humiliation. From the perspective of Islamic Criminal Law, such pranks are categorized as jarimah ta’zir, crimes that are harmful but whose punishments are not explicitly defined in primary texts, leaving sentencing to the discretion of the judge. This study contributes to the discourse by integrating modern digital behavior with classical Islamic legal theory. It also underscores the growing application of restorative justice as an alternative legal mechanism in resolving content-related offenses online, highlighting the need for preventive and rehabilitative legal strategies.